Qual é a resposta desta questão ?-3(×-5)-2(2×+1)=-8
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo a passo:
Respondido por
0
-3 (x-5) -2 c (2x1) = - 8
-3 (x-5) - 2x2 = - 8
-3 x + 15 - 4 = - 8
- 3 x + 11 = - 8
- 3 x = -8 - 11
- 3 x = 19
X= 19
3
-3 (x-5) - 2x2 = - 8
-3 x + 15 - 4 = - 8
- 3 x + 11 = - 8
- 3 x = -8 - 11
- 3 x = 19
X= 19
3
Perguntas interessantes
Português,
7 meses atrás
Biologia,
7 meses atrás
História,
7 meses atrás
Matemática,
8 meses atrás
Geografia,
8 meses atrás
Geografia,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás